My music, my voice: Musicality, culture and childhood in Vhavenda communities. (August 2016) - Emberly, Andrea; Davhula, Lusani Antoinette
The notion of children's "voices" is a construct used to frame the lack of power and agency that young people yield in their lives. However, representing children as "voiceless" overlooks how they employ tools, such as music, to voice their agency in dynamic, articulate, and meaningful ways. This collaborative article examines how children and young people in Vhavenda communities in South Africa utilize music to straddle their realities between tradition and change. Through this exploration, we will demonstrate how children and young people shape, embody, and challenge the lived and contemporary notions of what it means to be Vhavenda.